sin 2 2 0 ∘ + cos 2 5 0 ∘ + sin 2 0 ∘ cos 5 0 ∘ = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
@Potsawee Manakul Same method, upvoted! x
sin 2 2 0 ∘ + cos 2 5 0 ∘ + sin 2 0 ∘ cos 5 0 ∘ = cos 2 7 0 ∘ + cos 2 5 0 ∘ + cos 7 0 ∘ cos 5 0 ∘ = ( cos 7 0 ∘ + cos 5 0 ∘ ) 2 − cos 7 0 ∘ cos 5 0 ∘ = ( cos ( 6 0 + 1 0 ) ∘ + cos ( 6 0 − 1 0 ) ∘ ) 2 − cos ( 6 0 + 1 0 ) ∘ cos ( 6 0 − 1 0 ) ∘ = ( 2 cos 6 0 ∘ cos 1 0 ∘ ) 2 − ( cos 6 0 ∘ cos 1 0 ∘ − sin 6 0 ∘ sin 1 0 ∘ ) ( cos 6 0 ∘ cos 1 0 ∘ + sin 6 0 ∘ sin 1 0 ∘ ) = cos 2 1 0 ∘ − ( 2 1 cos 1 0 ∘ − 2 3 sin 1 0 ∘ ) ( 2 1 cos 1 0 ∘ + 2 3 sin 1 0 ∘ ) = cos 2 1 0 ∘ − 4 1 cos 2 1 0 ∘ + 4 3 sin 2 1 0 ∘ = 4 3 cos 2 1 0 ∘ + 4 3 sin 2 1 0 ∘ = 4 3 = 0 . 7 5
Great solution
Consider the identity a 3 − b 3 = ( a − b ) ( a 2 + b 2 + a b )
We have sin 3 2 0 ∘ − cos 3 5 0 ∘ = ( sin 2 0 ∘ − cos 5 0 ∘ ) ( sin 2 2 0 ∘ + cos 2 5 0 ∘ + s i n 2 0 ∘ c o s 5 0 ∘ )
So, we now need to evaluate
sin 2 0 ∘ − cos 5 0 ∘ sin 3 2 0 ∘ − cos 3 5 0 ∘
We now use the identity
sin 3 θ = 3 sin θ − 4 sin 3 θ cos 3 θ = 4 cos 3 θ − 3 cos θ
Now, sin 6 0 ∘ = 3 sin 2 0 ∘ − 4 sin 3 2 0 ∘ . . . . . . . . . . . . . . ( 1 ) cos 1 5 0 ∘ = 4 cos 3 5 0 ∘ − 3 cos 2 0 ∘ . . . . . . . . . . . . . . ( 2 )
Realizing cos 1 5 0 ∘ = − sin 6 0 ∘ , we rewrite (2) as:
− sin 6 0 ∘ = 4 cos 3 5 0 ∘ − 3 cos 2 0 ∘ . . . . . . . . . . . . . . ( 3 )
Adding (1) and (3), we have 0 = 3 ( sin 2 0 ∘ − cos 5 0 ∘ ) − 4 ( sin 3 2 0 ∘ − cos 3 5 0 ∘ )
So, sin 2 0 ∘ − cos 5 0 ∘ sin 3 2 0 ∘ − cos 3 5 0 ∘ = 4 3
which is 0 . 7 5
sin20=sin(50-30)=sin50cos30-sin30cos50=sqrt3/2sin50-1/2cos50=>. 1.(sqrt3/2sin50-1/2cos50)^2=3/4sin^2(50)+1/4cos^2(50)-sqrt3/2cos50sin50 si 2. sin20 cos50=(sqrt3/2sin50-1/2cos50) cos50 =>1.+2.=3/4
Problem Loading...
Note Loading...
Set Loading...
sin 2 2 0 ∘ + cos 2 5 0 ∘ + sin 2 0 ∘ cos 5 0 ∘ = ( sin 2 0 ∘ + cos 5 0 ∘ ) 2 − sin 2 0 ∘ cos 5 0 ∘ = ( sin 2 0 ∘ + sin 4 0 ∘ ) 2 − sin 2 0 ∘ cos 5 0 ∘ = ( 2 sin 3 0 ∘ cos 1 0 ∘ ) 2 − 2 1 ( sin 7 0 ∘ − sin 3 0 ∘ ) = cos 2 1 0 ∘ − 2 1 ( sin 7 0 ∘ − sin 3 0 ∘ ) = 2 cos 2 0 ∘ + 1 − 2 cos 2 0 ∘ + 2 sin 3 0 ∘ = 0 . 7 5